STUDY OF POSSIBLE ULCEROGENIC AND LOCAL EFFECTS OF BENFURAM - Kornienko, V.I.; Duchenko, E.A.; Ladohubets, E.V.; Ponomarenko, O.V.; Harkusha, I.V. (World of Medicine and Biology, 2018)
An important problem in the present-day pharmacology is formulation of new, more effective and safe pharmaceutical substances. Availability of various pharmacological activity types in new compounds can be evidence of the polytropic action of the studied chemical group derivatives. The previous studies have established the low toxicity of benfuram, the theobromine derivative, which has a wide range of pharmacological activity.The possible ulcerogenic effect of benfuram was studied on the model of ethanol ulcers, on animals that had starved for 24 hours. It was established that benfuram in the dose of 50 and 100 mg/kg did not cause damage to the mucous membrane of the stomach and the duodenum. The faint ulcerogenic effect of benfuram was only manifested in the dose of 200 mg/kg. In this dose, benfuram caused damage to the gastric mucosa in one animal, which makes 10%. The ulcerous index (UI) is 0.02, which is 10 times less than with acetylsalicylic acid administered.The study of benfuram ulcerogenic action was performed on a model of ethanol induced ulcers in experiments on white nonlinear rats weighing 180-190 g. Analysis of experimental results showed that benfuram in a dose of 35 and 100 mg/kg did not cause a significant change in the degree of ulceration in the gastric mucosa in comparison with the control group for which the ulcerative index was 2.2. Acetylsalicylic acid in the studied doses potentiated the ulcerogenic effect of ethanol. A significant effect was observed when acetylsalicylic acid was administered at a dose of 100 mg/kg (ulcerative index 3.2).The experimental study of the benfuram’s irritant action was performed in experiments on chinchilla breed rabbits, which were treated with 1% fine aqueous suspension of benfuram instilled into eyes, stabilized with a tween-80. It was established that 6 hours after benfuram instillation, the diameter of the eye pupil in animals did not change. In rabbits, benfuram did not cause swelling of the eyelids, corneal opacity, tears, eczema, toxicodermia, and conjunctivitis. One animal had moderate conjunctival hyperemia which had subsided for 5 hours. No changes were also observed in the eye conjunctival mucosa and in the pupil diameter a day after the instillation.Thus, the ulcerogenic effect of benfuram on the gastric mucosa of starving animals is only manifested in doses that exceed the ED50 by more than 5 times. Unlike acetylsalicylic acid, benfuram does not potentiate the ulcerogenic action of ethanol. Administering benfuram to animals kept in the natural environment during 14 days did not cause damage to the stomach and the duodenum mucosa.
Keywords: ulcerogenic; locally irritating effect; benofuram